If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -6(n + -4) = 56 Reorder the terms: 8 + -6(-4 + n) = 56 8 + (-4 * -6 + n * -6) = 56 8 + (24 + -6n) = 56 Combine like terms: 8 + 24 = 32 32 + -6n = 56 Solving 32 + -6n = 56 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + -6n = 56 + -32 Combine like terms: 32 + -32 = 0 0 + -6n = 56 + -32 -6n = 56 + -32 Combine like terms: 56 + -32 = 24 -6n = 24 Divide each side by '-6'. n = -4 Simplifying n = -4
| -2(x+4)=10-(1+x) | | -17=-2n+14-8n | | lwhx=0 | | lwhx= | | 7(2n+5)=6(9n+4)+8 | | -3(x-2y)=-3x-6y | | 2x-12=5x-3 | | (3+j*4)+(7-j*2)-(3-j*3)+j^5= | | a=lwx | | (10,-9)M=-2 | | 3-(2x+5)=21 | | q+(-9)=12 | | x/3-7=2 | | 0.2(x+40)+0.4x=17 | | 30=(-.08*250)+y | | 10a+17-13a+47=b | | 4+2x-2=8x+5-5x | | 0=-.08*x+50 | | 17x-10=17x-10 | | y=-.08*x+50 | | 99=6t-17t | | 11w-16w=-30 | | 4(9+2x)=4x+8 | | 4/5+x=3/7 | | 10k+5=6k-15 | | 8(t-2)+4t=6(2t+4)-11 | | 7-8(a+1)=8+a | | 5x-(2-3x)=2x-2 | | 5x-(2-3)=2x-2 | | 2(x+2)=2(x+5) | | 5x^2-60=0 | | 585+13x= |